Umang Folklore in Karo Society Around Umang Tanjung Pulo Cave of Karo District - Hidayati, Dyah; Hidayat, Hidayat; Khair Amal, Bakhrul (Interdisciplinary Social Studies, 2023)
Background: Karo people know Umang folklore for generations. Umang folklore is also framed in an archaeological object known as the Umang cave. The locus of this research is the area around Tanjung Pulo Umang cave, Tiganderket district, Karo regency, North Sumatra Province. The issue raised is whether Umang folklore is still known in this location, and whether the folklore is still relevant today. Aim: This research explored issues such as whether the Umang folklore is still known by the people around the Tanjung Pulo Umang cave and is the Umang folklore still relevant to the lives of the people around the Tanjung Pulo Umang cave today. Methods: This research is descriptive qualitative with an ethnographic approach. The methods used in data collection are observations, interviews, and literature studies. Findings: Umang folklore is still known around Tanjung Pulo Umang cave but is limited to people aged 40 years and over. And now the folklore is considered irrelevant anymore because of the progress of the times, education, religion, and technology.